Schools, pupils, and teachers. - Fleming, W. G. (Ontario's educative society, 1971)
Volume III explores the basic units in the educational system: student, teacher, and school. It examines the aims of education, historically and philosophically, and describes the development of various types of schools. The book provides an analysis of the use of educational media, a description of school buildings and equipment, among many other topics. An important part of the volume is a description of the evolution of the curriculum from the nineteenth century, with a detailed analysis of the changes made in such areas as science, the social sciences, and French.